2019
DOI: 10.1083/jcb.201809027
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Blos1 mRNA by IRE1 repositions lysosomes and protects cells from stress

Abstract: Cells respond to stress in the ER by initiating the widely conserved unfolded protein response. Activation of the ER transmembrane nuclease IRE1 leads to the degradation of specific mRNAs, but how this pathway affects the ability of cells to recover from stress is not known. Here, we show that degradation of the mRNA encoding biogenesis of lysosome-related organelles 1 subunit 1 (Blos1) leads to the repositioning of late endosomes (LEs)/lysosomes to the microtubule-organizing center in response to stress in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 48 publications
0
60
0
Order By: Relevance
“…XBP1s is a transcription factor that stimulates multiple genes with adaptive and cytoprotective functions to facilitate ER-stress mitigation (14)(15)(16). In addition to promoting XBP1 mRNA splicing, the IRE1 RNase degrades ER-targeted mRNAs-a process termed regulated IRE1-dependent decay, or RIDD-to abate translation (17,18), suppress apoptosis (19,20), and augment protective autophagy (21). Author Manuscript Published OnlineFirst on April 7, 2020; DOI: 10.1158/0008-5472.…”
Section: Introductionmentioning
confidence: 99%
“…XBP1s is a transcription factor that stimulates multiple genes with adaptive and cytoprotective functions to facilitate ER-stress mitigation (14)(15)(16). In addition to promoting XBP1 mRNA splicing, the IRE1 RNase degrades ER-targeted mRNAs-a process termed regulated IRE1-dependent decay, or RIDD-to abate translation (17,18), suppress apoptosis (19,20), and augment protective autophagy (21). Author Manuscript Published OnlineFirst on April 7, 2020; DOI: 10.1158/0008-5472.…”
Section: Introductionmentioning
confidence: 99%
“…The role of BLOS1 in this process is considered to be independent of BLOC-1 or BORC for the following reasons: (1) neither BLOC-1-deficient pa mice nor BORC-deficient Kxd1-KO mice showed reduced LDLR level; (2) KIF3A-KD cells resembled BLOS1 deficient phenotype both in LDLR level and abnormal movement of REs, indicating a kinesin-2-related function. But it remains possible that BLOS1 deficiency caused by dysfunction of BORC may further enhance LDLR degradation due to the proximity of ERC and perinuclearly clustered lysosomes since it has been reported that clustering LEs/lysosomes at the MTOC would generally enhance aggregate degradation and macroautophagy (Bae, Moore, Mella, Hayashi, & Hollien, 2019;Korolchuk et al, 2011). As for the complexity in kinesin motors and cargoes, it has been reported that one kinesin could use different adaptor proteins for various cargoes and different kinesins may transport one cargo on distinct microtubule tracks (Guardia et al, 2016;Hirokawa et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The role of BLOS1 in this process is considered to be independent of BLOC-1 or BORC for the following reasons: (1) neither BLOC-1-deficient pa mice nor BORC-deficient Kxd1-KO mice showed reduced LDLR level; (2) KIF3A-KD cells resembled BLOS1 deficient phenotype both in LDLR level and abnormal movement of REs, indicating a kinesin-2-related function. But it remains possible that BLOS1 deficiency caused by dysfunction of BORC may further enhance LDLR degradation due to the proximity of ERC and perinuclearly clustered lysosomes since it has been reported that clustering LEs/lysosomes at the MTOC would generally enhance aggregate degradation and macroautophagy (Bae, Moore, Mella, Hayashi, & Hollien, 2019;Korolchuk et al, 2011).…”
Section: Discussionmentioning
confidence: 99%